The Role of E-WOM in Stimulating Tourist Visits to the Bandung Zoo - Riksa Dinasti Sundari; Yadi Ernawadi (Jurnal Fokus Manajemen, 2023)
The purpose of this study was to examine the effect of the E-WOM dimension on revisit intention mediated by the destination image of Bandung Zoo tourists. The instruments used to collect data have passed validity tests based on both logical and empirical approaches. The characteristics of the respondents in this study were tourists with a minimum age of 17 years who had visited the Bandung Zoo at least once during the past year and had read E-WOM about the Bandung Zoo through internet media which were the objects assessed in this study as many as 100 people. The type of data in this study is included in the primary data. The data collection technique used is cross-sectional or one shot study. Data processing techniques through surveys using online questionnaires. The data analysis technique used is multiple linear regression using SPSS version 25 and using the Sobel test. Of the ten proposed research hypotheses, eight of them are supported by empirical data. The findings of this study indicate that E-WOM influences revisit intention directly or indirectly. Meanwhile, the use of other concepts to directly influence revisit intention can be proposed by future researchers. The results of this study are also useful for the management of the object being assessed and the similar tourism industry regarding the design of strategies to improve the quality of these attributes.